Modeling Denitrification: Can We Report What We Don't Know? - B. Grosz; A. Matson; K. Butterbach‐Bahl; T. Clough; E. A. Davidson; R. Dechow; S. DelGrosso; E. Diamantopoulos; P. Dörsch; E. Haas; H. He; C. V. Henri; et al. (AGU Advances, 2023)
Abstract Biogeochemical models simulate soil nitrogen (N) turnover and are often used to assess N losses through denitrification. Though models simulate a complete N budget, often only a subset of N pools/fluxes (i.e., N2O, NO3−, NH3, NOx) are published since the full budget cannot be validated with measured data. Field studies rarely include full N balances, especially N2 fluxes, which are difficult to quantify. Limiting publication of modeling results based on available field data represents a missed opportunity to improve the understanding of modeled processes. We propose that the modeler community support publication of all simulated N pools and processes in future studies.